Improving Optical Temperature Sensing Performance of Er(3+) Doped Y(2)O(3) Microtubes via Co-doping and Controlling Excitation Power - Wang, Xiangfu (Sci Rep, 2017)
This work presents a new method to effectively improve the optical temperature behavior of Er(3+) doped Y(2)O(3) microtubes by co-doping of Tm(3+) or Ho(3+) ion and controlling excitation power. The influence of Tm(3+) or Ho(3+) ion on optical temperature behavior of Y(2)O(3):Er(3+) microtubes is investigated by analyzing the temperature and excitation power dependent emission spectra, thermal quenching ratios, fluorescence intensity ratios, and sensitivity. It is found that the thermal quenching of Y(2)O(3):Er(3+) microtubes is inhibited by co-doping with Tm(3+) or Ho(3+) ion, moreover the maximum sensitivity value based on the thermal coupled (4)S(3/2)/(2)H(11/2) levels is enhanced greatly and shifts to the high temperature range, while the maximum sensitivity based on (4)F(9/2(1))/(4)F(9/2(2)) levels shifts to the low temperature range and greatly increases. The sensitivity values are dependent on the excitation power, and reach two maximum values of 0.0529/K at 24 K and 0.0057/K at 457 K for the Y(2)O(3):1%Er(3+), 0.5%Ho(3+) at 121 mW/mm(2) excitation power, which makes optical temperature measurement in wide temperature range possible. The mechanism of changing the sensitivity upon different excitation densities is discussed.